The senescence effect of zoledronate on three-dimensional oral mucosa model - Nur Bashira Shaharuddin,; Jones, Danial; Wen, Lin Chai (Penerbit Universiti Kebangsaan Malaysia, 2022)
Zoledronate (ZOL) is an antiresorptive bisphosphonate used to prevent bone loss in skeletal-related disorders, especially in patients with advanced cancer metastatic to bone. However, this medication led to an oral lesion known as medication-related osteonecrosis of the jaw (MRONJ) which also presents clinically as unhealing soft tissue in the jaw. Keratinocytes are thought to be a significant onset factor for MRONJ and recent findings have shown evidence of senescence in keratinocytes. However, little is known about the effect of senescence-associated inflammation that may cause age-associated tissue degeneration, which relates mainly to the expression of extracellular modulators including cytokines known as senescence-associated secretory phenotype (SASP). The aim of this experiment was to investigate the effect of ZOL treatment and senescence-associated secretory phenotype (SASP) if any, on a three-dimensional oral mucosa model (OMM) in which a novel modification was made to reflect the existence of basement membrane (BM) and lamina propria accurately. The ZOL dosage for the model was optimized by exposing the immortalized human oral keratinocyte line (OKF 6/TERT-2) and normal human oral fibroblasts (NHOF) to ZOL at increasing dosages and then histoarchitecture of OMM was examined. Analysis of the model’s histology showed significant epithelial thinning upon ZOL treatment and breakage of the BM accompanied by downward proliferation towards the lamina propria. A significant release of SASP molecules (MMP-3 and IL-8) was also detected upon treatment. Therefore, this study suggests that ZOL may impair healing at multiple types of tissues, originally from keratinocytes, by the deleterious effects of the senescence-associated inflammatory response.